Changes in Perceptions and Practices of Farmers and Pesticide Retailers on Safer Pesticide Use and Alternatives: Impacts of a Community Intervention in Chitwan, Nepal. (7th July 2017) - Vaidya, Abhinav; Gyenwali, Deepak; Tiwari, Sundar; Pande, Badri Raj; Jørs, Erik
Unsafe use of hazardous pesticides is a neglected public health problem in developing countries. This survey evaluates the effects of a training program to increase awareness on harmful effects of pesticides and to enhance capacity for safe handling involving 57 trained farmers, 98 neighboring farmers, 94 control farmers, and 23 pesticide retailers from villages in Chitwan, Nepal. Knowledge and attitude–related variables improved in all 3 farmer groups, with a significant trend of better knowledge and attitude from trained to neighboring to control farmers (in 14/16 [87.5%] variables). In practice, there were significant differences among the groups with a trend from trained to neighboring to control farmers (in 10/26 [38.5%] variables).The pesticide retailers also improved on knowledge and practice. In conclusion, training farmers and pesticide retailers improved their knowledge and practice, with possible positive effect on neighboring farmers and control villages as well. An improved extension service to farmers is recommended.